2019
DOI: 10.21608/ejhc.2019.26740
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Nursing Care Provided to Neonates Undergoing Phototherapy

Abstract: Background: Neonatal jaundice occurs in about 60% of neonates. If not managed properly, it can progress to severe neonatal jaundice leading to death or permanent disability. Aim of this study: To assess nursing care provided to neonates undergoing phototherapy. Design: A descriptive design was utilized in this study. Setting: The study was carried out in the neonatal intensive care units affiliated to Helwan General Hospital and Ain Shams University Obstetric Hospital. Subject:The study included 80 nurses work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 3 publications
1
2
0
Order By: Relevance
“…This may be explained as nurses' knowledge acquired only from their experience at NICU. This finding was supported with Ibrahim et al, (2019) who showed that more than two-thirds of the studied nurses in their study had poor knowledge as regard definition of neonatal jaundice and more than three-quarters of them had poor knowledge regarding clinical manifestations before educational intervention (24) . While this result was contradicted with Ahmed et al, (2017) who conducted study about assessment of nurses' knowledge and practice about neonatal jaundice and reported that majority of the studied nurses had good knowledge about definition of neonatal jaundice (25) .…”
Section: Subjects and Methodsupporting
confidence: 79%
“…This may be explained as nurses' knowledge acquired only from their experience at NICU. This finding was supported with Ibrahim et al, (2019) who showed that more than two-thirds of the studied nurses in their study had poor knowledge as regard definition of neonatal jaundice and more than three-quarters of them had poor knowledge regarding clinical manifestations before educational intervention (24) . While this result was contradicted with Ahmed et al, (2017) who conducted study about assessment of nurses' knowledge and practice about neonatal jaundice and reported that majority of the studied nurses had good knowledge about definition of neonatal jaundice (25) .…”
Section: Subjects and Methodsupporting
confidence: 79%
“…Identification of the neonate at risk, parent education and support, and nursing care for newborns receiving hyperbilirubinemia treatment are all crucial tasks performed by the neonatal nurse. The neonatal nurse is responsible for facilitating communication between parents, lab staff, doctors, and other members of the newborn care team (Ibrahim et al, 2019). During phototherapy, newborns need nursing care that include monitoring room temperature, positioning, body temperature, skincare, hydration, feeding, umbilical stump care, eye care, genital care, and nursing care that is based on evidence (Pandey, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…When phototherapy was used, only 2 of 833 such infants (0.24%) received exchange transfusions. Between January 1988 and October 2007, no exchange transfusions were needed in the neonatal intensive care unit at William Beaumont Hospital, in Royal Oak, Michigan, for 2425 infants who weighed less than 1500 g at birth (2) .Wash hands before and after any nursing procedure , Ensure that the premature body is exposed to light, Covering the eyes and genitals of the premature infant so as not to allow the passage of light, The distance of the light from the premature body is 10-30 cm, Turn off the lighting device when the baby is breast-feeding (breastfeeding) and when examining to protect the eyes of the baby, mother, and workers in neonatal care units from the influence of light (3) .Remove the eye cover when feeding, Giving intravenous fluids according to the doctor's instructions, and avoiding exposure of the newborn to dehydration, Changing the newborn's position in the incubator to ensure that the rest of the body is exposed to light and to avoid skin ulcers, Explaining the importance of phototherapy and breastfeeding to the newborn's parents to help them accept the treatment and nursing documentation after any nursing procedure and intervention (4) .…”
Section: Introductionmentioning
confidence: 99%